2019
DOI: 10.1002/jcph.1438
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Modeling Suggests Limited Drug‐Drug Interaction for Fesoterodine When Coadministered With Mirabegron

Abstract: 5‐Hydroxymethyl tolterodine (5‐HMT; the active fesoterodine metabolite) is metabolized via the cytochrome P450 (CYP) 2D6 and CYP3A pathways. Mirabegron is a moderate CYP2D6 inhibitor and weak CYP3A inhibitor. Potential drug‐drug interactions (DDIs) following coadministration of these 2 overactive bladder treatments were estimated using physiologically based pharmacokinetic models, developed and verified by comparing predicted and observed pharmacokinetic profiles from clinical studies. Models predicted and ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(103 reference statements)
0
2
0
1
Order By: Relevance
“…For fesoterodine and mirabegron, this has been predicted based on well‐established physiologically based pharmacokinetic models (Simcyp). The increase in the peak plasma concentration and the area under the plasma concentration‐time curve of 5‐HMT following concomitant administration of mirabegron and fesoterodine was <25%, which was not considered to be a clinically relevant drug‐drug interaction for fesoterodine …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For fesoterodine and mirabegron, this has been predicted based on well‐established physiologically based pharmacokinetic models (Simcyp). The increase in the peak plasma concentration and the area under the plasma concentration‐time curve of 5‐HMT following concomitant administration of mirabegron and fesoterodine was <25%, which was not considered to be a clinically relevant drug‐drug interaction for fesoterodine …”
Section: Discussionmentioning
confidence: 99%
“…Evidence supports that fesoterodine and 5‐HMT both bind bladder and detrusor tissue with higher affinity than the parotid gland competitively and reversibly, indicating their selectivity for the target tissues. Another modeling and simulation study showed that when fesoterodine and mirabegron were coadministered, predicted changes in 5‐HMT plasma concentrations were clinically insignificant, and did not warrant changes in the recommended daily dose of fesoterodine when given with mirabegron . Notably, no differences were observed in side effects reported in a clinical trial by treatment groups receiving nonselective or selective antimuscarinics alongside a β 3 agonist .…”
Section: Discussionmentioning
confidence: 99%
“…Известно, что активация β-адренорецепторов нор адреналином, высвобождаемым из симпатических нервов, повышает уровень циклического аденозинмонофосфата в гладких мышцах, что является ключевым триггером для их расслабления [19]. В этой связи весьма перспективными представляются результаты первого исследования эффективности совместного применения при ГМП М 2 -, М 3 -холиноблокатора фезотеродина и β 3 -адреномиметика мирабегрона [20].…”
Section: Introductionunclassified